1996
DOI: 10.1002/(sici)1096-9837(199607)21:7<589::aid-esp659>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Wind-Tunnel Modelling of the Influence of Vegetation Structure on Saltation Threshold

Abstract: The influence of vegetation structure on saltation threshold was investigated using uniformly spaced arrays of non-erodible roughness elements on a bed of erodible sand in an wind tunnel. Structural variables tested using arrays of solid cylinders included element aspect ratio (height/diameter) and lateral cover (total frontal-silhouette area per unit ground area). In agreement with previous studies, increase in saltation threshold above the value for bare sand was strongly related to lateral cover. Increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
78
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(87 citation statements)
references
References 36 publications
7
78
2
Order By: Relevance
“…Taylor [92] found that drag coefficients decreased exponentially as the porosity of a two-dimensional barrier increased, but Grant and Nickling [91] demonstrated that a peak in drag coefficient occurred at an intermediate optical porosity (~20%) for three-dimensional trees. It has been shown that elements with a porosity less than 20% act to enhance wind speed recovery in their lee [68,[93][94][95], so elements with intermediate porosity strike a compromise between shear stress reduction and the downwind distance for which it is effective [96,97]. However, even porosity values of 50% can cause wake effects to extend to at least 50 h downwind of a windbreak [98].…”
Section: Trapping Of Windborne Sedimentmentioning
confidence: 99%
See 3 more Smart Citations
“…Taylor [92] found that drag coefficients decreased exponentially as the porosity of a two-dimensional barrier increased, but Grant and Nickling [91] demonstrated that a peak in drag coefficient occurred at an intermediate optical porosity (~20%) for three-dimensional trees. It has been shown that elements with a porosity less than 20% act to enhance wind speed recovery in their lee [68,[93][94][95], so elements with intermediate porosity strike a compromise between shear stress reduction and the downwind distance for which it is effective [96,97]. However, even porosity values of 50% can cause wake effects to extend to at least 50 h downwind of a windbreak [98].…”
Section: Trapping Of Windborne Sedimentmentioning
confidence: 99%
“…However, even porosity values of 50% can cause wake effects to extend to at least 50 h downwind of a windbreak [98]. The sediment trapping mechanism of plants (see Section 2.1.3) also depends on plant porosity [53,54,96], with wind tunnel (e.g., [97]) and field (e.g., [91]) experiments showing that the trapping effect of vegetation is maximised at intermediate values of porosity (20-40%). Using wire mesh structures, Gillies et al [86,99] showed that porous elements have a greater potential for modulating sediment flux than solid elements in large spatial arrays.…”
Section: Trapping Of Windborne Sedimentmentioning
confidence: 99%
See 2 more Smart Citations
“…Musick et al, 1996), where strips of double-sided sticky tape were placed flat on the bed surface near the downwind end of the test tray to capture moving grains by adhesion. This initiation of sand grains was observed visually.…”
Section: Wind Tunnel Testsmentioning
confidence: 99%